Realizacja zaleceń lekarza rodzinnego przez pacjentów w wybranych jednostkach chorobowych = Implementation of the recommendations of the General Practice Doctor by patients in selected disease entities. - Ewa Warchoł-Sławińska; Marzena Furtak-Niczyporuk; Krzysztof Włoch; Agata Żuber (Kazimierz Wielki University, 2016)
Warchoł-Sławińska Ewa, Furtak-Niczyporuk Marzena, Włoch Krzysztof, Żuber Agata. Realizacja zaleceń lekarza rodzinnego przez pacjentów w wybranych jednostkach chorobowych = Implementation of the recommendations of the General Practice Doctor by patients in selected disease entities. Journal of Education, Health and Sport. 2016;6(12):171-183. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.192883 http://ojs.ukw.edu.pl/index.php/johs/article/view/4043         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.11.2016. Revised 22.11.2016. Accepted: 06.12.2016.       Realizacja zaleceń lekarza rodzinnego przez pacjentów w wybranych jednostkach chorobowych   Implementation of the recommendations of the General Practice Doctor by patients in selected disease entities     Ewa Warchoł-Sławińska*, Marzena Furtak-Niczyporuk*, Krzysztof Włoch*, Agata Żuber**   *Katedra i Zakład Zdrowia Publicznego Uniwersytet Medyczny w Lublinie **Absolwent Uniwersytetu Medycznego w Lublinie         Adres do korespondencji: Katedra i Zakład Zdrowia Publicznego Uniwersytet Medyczny w Lublinie Lublin 20-093, ul. Chodźki 1     Streszczenie   Wprowadzenie: Rolą podstawowej opieki zdrowotnej jest opanowanie czynników ryzyka sprzyjających chorobom cywilizacyjnym, jak choroby układu krążenia, czy choroby metaboliczne. Dużą rolą lekarza rodzinnego jest promocja zdrowia, która skupia się na edukacji zdrowotnej społeczeństwa poprzez przekazywanie wiedzy i kompetencji pozwalających na zwiększenie kontroli nad zdrowiem i jego pomnażanie.   Cel pracy: Celem pracy była ocena realizacji zaleceń lekarza rodzinnego przez pacjentów w wybranych jednostkach chorobowych. Badanie skupiało się na odpowiedzi na pytanie w jakim stopniu pacjenci z wybranymi jednostkami chorobowymi przestrzegają zaleceń lekarza rodzinnego?   Materiał i metody: W badaniu opinii publicznej zastosowano metodę sondażu diagnostycznego, przy zastosowaniu techniki badawczej w formie ankiety. Badanie przeprowadzono przy użyciu autorskiego kwestionariusza ankiety zawierającego 38 pytania. Badaniem objęto 99 pacjentów, z 2 przychodni podstawowej opieki zdrowotnej, z obszaru województwa lubelskiego.   Wyniki i wnioski: Z badań wynika potrzeba zwiększenia działań edukacji zdrowotnej w obszarach promocji zdrowego stylu życia. Szczególnie widoczna jest potrzeba zwiększenia promocji badań przesiewowych, wyeliminowania używek, zwiększenia aktywności fizycznej, zwiększenia promocji zdrowej i zbilansowanej diety zawierającej owoce i warzywa. Ma się to przyczynić do zwiększenia odsetka populacji pozostającej w dobrym zdrowiu. Przedmiotowe badanie pokazało, że z grupy 99 badanych aż 52% z nich oceniło swoje zdrowia przeciętnie i źle. Dlatego najważniejszą tu rolę będzie miał lekarz rodzinny, gdyż najczęściej w pierwszej kolejności właśnie do niego udaje się pacjent ze swoim problemem.     Słowa kluczowe: podstawowa opieka medyczna, lekarz rodzinny.   Abstract   Introduction: The role of primary health care is to reduce the risk factors for lifestyle diseases, such as cardiovascular, and metabolic diseases. An important role of the family doctor is the health promotion, which focuses on health education through the transfer of knowledge and competence to increase control over one's health and its multiplication. Aim: The aim of this study was to assess the implementation of the recommendations of the family doctor by patients in selected disease entities. The study focused on responses to the question of the extent to which patients with selected disease units carried out the recommendations of General Practice Doctor.   Material and Methods: The survey of public opinion used diagnostic survey method, using a research technique in the form of a questionnaire. The study was conducted using a proprietary questionnaire containing 38 questions. The study included 99 patients of 2 primary care clinics, from the Lublin province. The results and conclusions: The research shows the need to increase health education activities in the areas of promoting healthy lifestyles. Particularly evident is the need to increase the promotion of screening, eliminating stimulants, increasing physical activity, increase the promotion of a healthy and balanced diet containing fruits and vegetables. This should contribute to increase the percentage of the population remains in good health. These study showed that 52% of the respondents from the group of 99 patients rated their health on average and bad. The most important role in improving this situation will be filled by a family doctor, because usually he is a person to which patients go first to solve their health problems.   Keywords: primary health care, General Practice Doctor.